Method for Improving Spatial Resolution and Amplitude by Optimized Deskew Filter in Long-Range OFDR - Yang Du; Tiegen Liu; Zhenyang Ding; Bowen Feng; Xiaobo Li; Kun Liu; Junfeng Jiang (IEEE Photonics Journal)
We present a method for improving the spatial resolution and the amplitude by an optimized deskew filter in long-range optical frequency-domain reflectometry (OFDR). In a previous deskew-filter method, as the nonlinear phase estimated from an auxiliary interferometer is used to compensate for the nonlinearity effect in the beating signals generated from a main OFDR interferometer, the spatial resolution and amplitude of the reflection peak in a long range (i.e., 80 km) are deteriorated by a residual nonlinearity effect due to the estimation inaccuracy of the nonlinear phase. In the proposed optimized deskew-filter method, the estimation accuracy of the nonlinear phase is improved by the higher orders of Taylor expansion and the high accuracy of the estimation of the time delay in the auxiliary interferometer using a cepstrum. We experimentally demonstrate that the amplitude of a reflection peak at 80 km increases by 20.5 dB and that the spatial resolution is up to 80 cm, which is about 187 times enhancement when compared with that of the same OFDR trace without nonlinearity compensation.